Determinants of Inflation in the Local Economy - Jaka Sriyana (ETIKONOMI, 2018)
This research analyzes the determinants of inflation rate in the local economy. It uses co-integration and vector error correction to capture the long and short run relationship between inflation rate and other economic variables. We find that the determinants of inflation rate in Yogyakarta are minimum wage, economic growth, and monetary variables indicated by BI-rate.  More finding, exchange rate also contributes to the price change. This research finds evidence of long-run causality between minimum wage and inflation and unidirectional relationship from wage to inflation in the short run. This finding confirms the proposition of non-neutrality wage on price changes. The inflation rate in the local economy depends not only on the regional indicator but also depends on international changes reflected in the exchange rate. Monetary variable indicated by BI- rate also partially contributes to the price changes at the local level. Overall, the local government has successfully managed the price changes.DOI: 10.15408/etk.v17i1.7146